Peranan Perbadanan Pembangunan Ekonomi Sarawak (SEDC) Sibu Dalam Pemberdayaan Ekonomi Masyarakat - Muhamad Nasharudin Bin Safiriee; Ratna Dewi (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to determine the forms of community, the process and changes and results achieved by SEDC Sibu in economic empowerment for the Sibu community. Based on these objectives, what will be the main discussion in this research is how SEDC Sibu plays a role in the economic empowerment efforts of the Sibu community. This study uses qualitative research methods, namely by using descriptive study methods. As a result of research findings and analysis, (1) SEDC Sibu has carried out several forms of economic empowerment programs that are in the form of loan assistance, training, and guidance such as the Small and Simple Industrial Loans Scheme (SPIKS), Incubator Centers and Business Guidance (PIBU), Training and Mentoring Guidance, and so forth. (2) The process carried out by SEDC Sibu are by holding deliberations in planning programs, formulating program plans, forming program implementation teams, and implementing programs. (3) The program that has been run successfully is based on indicators obtained from the field, namely increasing the income of the whole day, the community can manage all its affairs independently, and the community can solve problems with their ability and authority.